2008
DOI: 10.1590/s1980-57642009dn20100007
|View full text |Cite
|
Sign up to set email alerts
|

Functional communication ability in frontotemporal lobar degeneration and Alzheimer's disease

Abstract: Functional communication is crucial for independent and efficient communicative behavior in response to every day activities. In the course of dementia progression, cognitive losses may impair these abilities. For this reason, functional communication assessment should be part of a formal assessment to quantify and qualify the impact of deficiency on patients’ lives.ObjectiveTo compare functional communication abilities in fronto-temporal lobar degeneration (FLTD) and Alzheimer’s disease (AD).MethodsSix AD pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 14 publications
0
6
0
3
Order By: Relevance
“…The Direct Assessment of Functional Performance (DAFS) ( 245 ) was administered for the study of patients with FTD ( 238 ) (unlike the DAD, this is a performance-based test). In addition, Carvalho et al ( 246 ) used the Functional Assessment of Adult Communicative Skills (Asha-Facs) ( 247 ) in patients with FTD and AD. The results showed similar performances in both groups of patients ( 246 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Direct Assessment of Functional Performance (DAFS) ( 245 ) was administered for the study of patients with FTD ( 238 ) (unlike the DAD, this is a performance-based test). In addition, Carvalho et al ( 246 ) used the Functional Assessment of Adult Communicative Skills (Asha-Facs) ( 247 ) in patients with FTD and AD. The results showed similar performances in both groups of patients ( 246 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Carvalho et al ( 246 ) used the Functional Assessment of Adult Communicative Skills (Asha-Facs) ( 247 ) in patients with FTD and AD. The results showed similar performances in both groups of patients ( 246 ). Finally, in Chile, the T-ADLQ showed promising results for evaluating functional impairment in FTD ( 243 ).…”
Section: Resultsmentioning
confidence: 99%
“…Two studies failed to find differences among patients diagnosed with FTLD and AD on assessments of functionality. Carvalho et al [ 13 ] found no significant difference in functional communication between AD and FTLD patients. Similarly, Bahia et al [ 14 ] found no significant differences between patients with AD and FTLD on DAD scores.…”
Section: Discussionmentioning
confidence: 99%
“…Estes pacientes têm como característica principal, nas fases iniciais da doença, prejuízos diretos no desempenho de funções executivas, sobretudo na tomada de decisão, havendo alentecimento nessa função cognitiva (Allegri et al, 2001 (Dubois et al, 2000;Kertesz et al, 2000) e a Entrevista Executiva EXIT-25 (Royall et al, 1992). Bahia et al (2008) Para o diagnóstico de DFTvc, ressalta-se que tanto a neuroimagem estrutural (tomografia computadorizada ou ressonância magnética de crânio) quanto funcional (tomografia por emissão de fóton único-SPECT ou tomografia por emissão de pósitrons-PET) podem ser normais nas fases iniciais da doença, mesmo quando o paciente apresenta alteração comportamental evidente (Eslinger et al, 2012).…”
Section: Degeneração Lobar Frontotemporal (Dlft) E Seus Subtipos: Epiunclassified
“…Em Carvalho et al (2008), não houve diferença em aspectos da comunicação funcional entre pacientes com DA e DLFT. Bahia et al (2008) também não encontraram diferenças significativas entre pacientes com DA e DLFT para os escores da DAD. Na amostra, a DAD não apresentou boa acurácia no diagnóstico diferencial entre estes tipos demências.…”
Section: Desempenho Cognitivo E Funcional De Pacientes Com Dftvcunclassified